Endometrial Profile of Tamoxifen and Low-dose Estradiol Combination Therapy - Wood, Charles E. (2010)
PURPOSE: Combination estrogen+progestin therapy has been associated with increased breast cancer risk in postmenopausal women. Selective estrogen receptor modulators (SERMs) are potential alternatives to progestins, although endometrial safety of estrogen+SERM co-therapies is not known. The goal of this study was to evaluate the endometrial profile of low-dose estradiol and the SERM tamoxifen alone and in combination. EXPERIMENTAL DESIGN: Twenty-four postmenopausal female cynomolgus macaques were randomized by social group to receive placebo, low-dose micronized estradiol (E2, 0.25 mg/1800 kcal), the SERM tamoxifen (Tam, 20 mg/1800 kcal), or E2+Tam for 4 months in a parallel-arm design. RESULTS: Tamoxifen alone resulted in overlapping but distinct effects compared to E2. Both E2 and Tam increased uterine weight and endometrial thickness, while only E2 increased endometrial proliferation. Morphologic effects were similar for Tam and E2+Tam, which both induced stromal fibrosis and cystic change. Tamoxifen inhibited E2-induced proliferation and expression of genes related to cell cycle progression while exhibiting mixed agonist and antagonist effects on gene markers of estrogen receptor activity. The gene expression profile for E2+Tam was distinct from either E2 or Tam alone but dominated by the Tam effect for estrogen-regulated genes. Tam also attenuated E2 effects on both vaginal maturation and cervical epithelial height. CONCLUSIONS: These findings characterize a novel phenotype resulting from estrogen+SERM co-therapy. The predominance of Tam effects on endometrial proliferation, morphology, and transcriptional profiles suggests that endometrial risks for E2+Tam may be similar to Tam alone.